The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.12693/aphyspola.118.212
|View full text |Cite
|
Sign up to set email alerts
|

Charge and Orbital Order in Transition Metal Oxides

Abstract: A short introduction to the complex phenomena encountered in transition metal oxides with either charge or orbital or joint charge-and-orbital order, usually accompanied by magnetic order, is presented. It is argued that all the types of above ordered phases in these oxides follow from strong Coulomb interactions as a result of certain compromise between competing instabilities towards various types of magnetic order and optimize the gain of kinetic energy in doped systems. This competition provides a natural … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 178 publications
(295 reference statements)
2
13
0
Order By: Relevance
“…The detection of the complex magnetic structures in strongly correlated electron systems by X-ray diffraction [56,57] can be used to support the association of the spin signal to polaronic distortions. The new mesoscopic phase separation with scale free spatial correlation for spin stripes order found here in nickelates is in agreement with previous indications [53][54][55][56][57][58][59] and it provides the experimental smoking gun evidence that the spin ordering in spin stripes phase in nickelates is near a quantum critical point. A similar spatial fractal landscape has been found in cuprates [46][47][48][49][50][51][52] and in other oxides near a quantum phase transition as in VO 2 [60][61][62][63], in ruthenates [64,65], and in diborides [66,67].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The detection of the complex magnetic structures in strongly correlated electron systems by X-ray diffraction [56,57] can be used to support the association of the spin signal to polaronic distortions. The new mesoscopic phase separation with scale free spatial correlation for spin stripes order found here in nickelates is in agreement with previous indications [53][54][55][56][57][58][59] and it provides the experimental smoking gun evidence that the spin ordering in spin stripes phase in nickelates is near a quantum critical point. A similar spatial fractal landscape has been found in cuprates [46][47][48][49][50][51][52] and in other oxides near a quantum phase transition as in VO 2 [60][61][62][63], in ruthenates [64,65], and in diborides [66,67].…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, the phase separation reported in this work could be assigned also to the liquid-striped liquid phase separation in liquids of anisotropic polarons similar to the liquid-striped liquid phase separation in water [49,50]. The anisotropy of polaron clusters in nickelates is assigned here to misfit strain [51,52] and orbital degrees of freedom [53][54][55]. The detection of the complex magnetic structures in strongly correlated electron systems by X-ray diffraction [56,57] can be used to support the association of the spin signal to polaronic distortions.…”
Section: Discussionsupporting
confidence: 58%
“…It will be shown that a rather exotic behaviour of the RVO 3 perovskites cannot be understood without including the spin-orbital entangled states. This point of view is supported by several experimental observations: (i) the thermal evolution of the optical spectral weights [25], (ii) the phase diagram of the RVO 3 perovskites [21], and (iii) the observed dimerization in the magnon spectra of YVO 3 [26].An interesting situation arises also in doped Mott insulators, where doped holes introduce charge degrees of freedom which perturb the orbital order and frequently lead to phases with coexisting spin, charge and orbital order [27]. When orbital degrees of freedom are quenched, one finds that hole propagation occurs in the t-J model via a quasiparticle state that emerges due to quantum fluctuations in the spin background [28].…”
mentioning
confidence: 86%
“…Investigation of doped manganites is challenging as the Jahn-Teller distortions may lead to the charge order which will also favour particular orbital order [1,27]. To make the complex situation in doped manganites tractable in the theory, several theoretical papers were focused in past on single-layer and double-layer manganites as the description of quasi two-dimensional (2D) systems was simpler than the one necessary for three-dimensional (3D) doped perovskite manganites (see for example [11] and the references therein).…”
Section: Introductionmentioning
confidence: 99%